New Therapeutic Strategies in the Second Line Setting of Advanced or Metastatic Pancreatic Adenocarcinoma - Ramfidis, Vasilis Stefanos; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is a lethal disease and its prognosis remains dismal. The modest results of existing available treatments in the second line setting reveal the need of new therapeutic strategies. In this year’s American Society of Clinical Oncology (ASCO) Annual Meeting two remarkable trials and one retrospective analysis were presented regarding this vulnerable group of patients. According to the published results, docetaxel plus oxaliplatin (Abstract #4034), selumetinib plus erlotinib (Abstract #4014) and nab-paclitaxel (Abstract #e15057) have shown promising efficacy and manageable toxicity that should be elucidated and confirmed by new prospective, large, randomized trials. Image: Therapeutic strategies in second line setting of advanced or metastatic pancreatic adenocarcinoma. <!–[endif] –>